2004
DOI: 10.1021/jo030367x
|View full text |Cite
|
Sign up to set email alerts
|

An Effective Use of Benzoic Anhydride and Its Derivatives for the Synthesis of Carboxylic Esters and Lactones:  A Powerful and Convenient Mixed Anhydride Method Promoted by Basic Catalysts

Abstract: Various carboxylic esters are obtained at room temperature in excellent yields with high chemoselectivities from nearly equimolar amounts of carboxylic acids and alcohols using 2-methyl-6-nitrobenzoic anhydride with triethylamine by the promotion of a basic catalyst such as 4-(dimethylamino)pyridine. A variety of lactones are also prepared in high yields at room temperature from the corresponding omega-hydroxycarboxylic acids with use of 2-methyl-6-nitrobenzoic anhydride in the presence of 4-(dimethylamino)pyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
237
0
10

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 401 publications
(255 citation statements)
references
References 23 publications
4
237
0
10
Order By: Relevance
“…The subsequent macrolactonization of 9 was achieved by employing the Shiina method [13][14][15][16][17] [2-methyl-6-nitrobenzoic anhydride (MNBA) (1.3 equiv), 4-dimethylaminopyridine (DMAP) (3.0 equiv), CH 2 Cl 2 (1.0 mM), rt, 12 h], which resulted in the desired cyclization product 17 in 85% yield. Finally, simultaneous S-Tr deprotection and internal disulfide bond formation in 17 (95%), followed by the deprotection of the TBS group in the resulting disulfide 18 (90%) furnished thailandepsin B (2) …”
Section: Resultsmentioning
confidence: 99%
“…The subsequent macrolactonization of 9 was achieved by employing the Shiina method [13][14][15][16][17] [2-methyl-6-nitrobenzoic anhydride (MNBA) (1.3 equiv), 4-dimethylaminopyridine (DMAP) (3.0 equiv), CH 2 Cl 2 (1.0 mM), rt, 12 h], which resulted in the desired cyclization product 17 in 85% yield. Finally, simultaneous S-Tr deprotection and internal disulfide bond formation in 17 (95%), followed by the deprotection of the TBS group in the resulting disulfide 18 (90%) furnished thailandepsin B (2) …”
Section: Resultsmentioning
confidence: 99%
“…The residue was purified with flash column chromatography (SiO 2 , n-hexane-EtOAc=4 : 4,5,6,7-Tetraf luoro-2-(4-methoxybenzyloxy)-3-(2,2,2-trifluoroethoxy)-3-trifluoromethylisoindolin-1-one (33) According to the procedure described for the preparation of ether 32 from alcohol 31 in which 2,2,2-trifluoroenthanol was used as the alcohol instead, alcohol 31 (1.00 g, 2.35 mmol) was converted into ether 33 (0.593 g, 50%). 35) b, 36) g, 37) h, 38) j, 39) and k 40) were prepared following the reported procedures. General Procedure for Benzoate from Alcohol (Procedure C) 3-(4-Methoxyphenyl)propyl Benzoate (36c) To a solution of 3-(4-methoxyphenyl)-1-propanol 42c (1.66 g, 10.0 mmol) in CH 2 Cl 2 (20 mL), BzCl (1.39 mL, 12.0 mol) and pyridine (1.93 mL, 24.0 mmmol) were added at 0°C.…”
Section: General Procedures For Hydrogenolysis Of Benzyl Ether (Procedmentioning
confidence: 99%
“…Attempted macrolactonization using the Yamaguchi protocol furnished the requisite 140 in 56% yield for the two steps. After several attempts, it was found that the Shiina procedure 75,76) gave excellent results. Thus, treatment of a solution of 138 in CH 2 Cl 2 with 2-methyl-6-nitrobenzoic acid anhydride (139) and 4-dimethylaminopyridine (4-DMAP) at room temperature produced 140 in 92% yield.…”
Section: )mentioning
confidence: 99%